Spanish for the rest of us - Harvey, William C. (McGraw Hill, 2021)
"If you're one of the rest of us, this practical guide is for you! You will learn Spanish not by memorizing boring grammar rules, but by focusing on everyday, practical language. Author William Harvey emphasizes the most-often-used Spanish words and phrases, and reveals numerous language-learning tips that provide shortcuts to effective communication. And this lively, informal program is supported by audio recordings (online and via mobile app) to give you complete confidence in your Spanish pronunciation. Whether you need to communicate with Spanish speakers at work, in social situations, or on your travels, Spanish for the Rest of Us is the quick and easy way to understand and make yourself understood in Spanish!" --Back cover.